Adding а thiazide diuretic to combined antihypertensive therapy is clinically reasonable - V. I. Makolkin (Кардиоваскулярная терапия и профилактика)
The article describes the reasons for including thiazide and thiazide-like diuretics into combined antihypertensive therapy, with a combination of a beta-adrenoblocker (BAB) bisoprolol and a thiazide diuretic (TD) hydrochlorothiazide as an example. Diuretics should be administered in the doses not affecting glucose tolerance and lipid metabolism. Using Lodoz® medication as an example, the author stresses the need for combining D with various BAB doses, which could increase therapeutic potential while administering combined antihypertensive therapy.